Development and Simulation of a Rotor Flux- Oriented Control Scheme for Efficiency Improvement in a Three Phase Induction Motor - Olarinoye, G. A.; Balogun, F. O.; Abubakar, A. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
The efficiency of induction motor drives under variable operating load and speed conditions can be improved by developing an algorithm that compute the optimum flux in the motor and commands a voltage that drives the motor at maximum efficiency for any given load and speed. This approach also helps to achieve significant amount of savings in electric energy consumption. In this paper, a method to optimize the flux of a three-phase induction motor and thereby maximize its efficiency for each load torque applied at a given speed, was developed. Mathematical models for the conventional rotor flux-oriented control scheme, total power loss as a function of rotor flux and for optimum flux as a function of operating speed and load torque were analytically derived. A MATLAB/Simulink model of the proposed rotor flux optimization scheme was developed to verify the analyses set forth for a typical three-phase Induction Motor. The results of the proposed method were compared with those of the conventional rotor flux control method and direct torque control (DTC) method in terms of loss reduction and efficiency for the same induction motor. The proposed rotor flux optimization scheme achieved 8.51% improvement in efficiency compared to the conventional rotor flux control scheme at a speed of 250 rad/s for a load torque of 3Nm. It also achieved 5.01% improvement in efficiency compared to the optimized DTC control scheme for the same speed and load torque. At a lower speed of 150 rad/s, power loss reduced by 17.1% while efficiency was higher by 5.7% for a load torque of 3Nm under the proposed scheme as compared to the optimized DTC scheme